Pengaruh Dana Pihak Ketiga, Non Performing Financing Terhadap Jumlah Pembiayaan Bagi Hasil Perbankan Syariah di Indonesia dengan tingkat Bagi Hasil sebagai variabel Moderating - Nursantri Yanti (Jurnal Riset Akuntansi dan Bisnis, 2020)
In its operations, Islamic banks have one of the most important business activities, namely channeling funds to the public which is often referred to as financing. Bank business activities in the form of financing with profit sharing principle are a form of economic equality in accordance with sharia guidelines, because their activities are proven to support the circulation of assets and channel them productively. But in reality, Islamic banks are more dominant in distributing consumptive funds through buying and selling based financing. This study analyzes and tests whether Thirdh Party Funds, Non Performing Financing can affect the Profit Sharing Financing with Profit Sharing Rate as a moderating variable. The sample used in this study is monthly data on DPK, NPF, Profit Sharing and Profit Sharing Funding from 2015 to 2019. After processing the data using multiple linear regression tests and residual tests the research results obtained at alpha 5% which shows that DPK and NPF have a positive and significant effect on the amount of profit-sharing based financing by testing partially or simultaneously.